(untitled) (Journal of the College of Basic Education, 2022)
The present study was conducted to investigate the antimicrobial activity of the hot water and the hot ethanolic extracts of Thuja orientalisagainst some pathogenic microorganisms (Staphylococcus aureus, Pseudomonas aeruginosa, Eschericha coli, Proteus mirrablis, Salmonilla typhi, Klebsiella pneumoniae, Bacillus cereus, Bacillus subtilus, Acinobacter, Staphylococcus epidermidis and Candida albicans). Results showed that both the water and alcoholic extracts of this plant exertmarked inhibitory effect against all the bacterial isolates and yeast and at different ratio, and it was shown that ethanolic extract was more effective in microbial inhibition than the water extract. Maximum inhibition (16 mm) was recorded against Staphylococcus aureus and Candida albicans with the hot water extract, while maximum inhibition was seen against Bacillus cereus by the hot alcoholic extract.